1993
DOI: 10.1159/000263847
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Misdiagnosis of Intrauterine Growth Retardation for Preterm Elective Cesarean Section

Abstract: We studied the consequences of misdiagnosis of intrauterine growth retardation (IUGR) for preterm elective cesarean section among live singleton newborns in two teaching hospitals in Paris between 1978 and 1983. The population studied comprised the 16,540 babies who were normal for date, according to the 10th percentile of the reference curve established in this population. For 118 of these infants, IUGR had been diagnosed during pregnancy. The preterm elective cesarean section rate was 12.7% among newborns fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Our analysis of the indications for induction and pre‐labour caesareans also support this interpretation. One previous study from the 1990s also documented higher rates of caesarean section among false positives in two tertiary centres …”
Section: Discussionmentioning
confidence: 84%
“…Our analysis of the indications for induction and pre‐labour caesareans also support this interpretation. One previous study from the 1990s also documented higher rates of caesarean section among false positives in two tertiary centres …”
Section: Discussionmentioning
confidence: 84%
“…Therefore to avoid one perinatal death it would be necessary to perform 1000 umbilical Doppler examinations. Furthermore, benefit may be outweighed by the consequences of the false positives 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neonatal admission to the NICU was 2.2 times more likely in the FP group than in the TN group, which may be due to planned early induction of delivery (before 37 weeks) and early elective Cesarean section for fetal indication. The negative impact of SGA screening has been described previously by Ringa et al . in 1993, who showed that a larger number of interventions performed for SGA were related to the findings at ultrasound screening.…”
Section: Discussionmentioning
confidence: 55%